Reliability and validity of a wall slide test for monitoring growth-related lower limb pain in elite youth footballers - Blanchard, S.; Holden, S.; Dadd, L.; Cumming, S.; Williams, S. (Frontiers in Psychology, 2026)
Objectives To develop and evaluate the reliability and validity of a novel Wall Slide Test for monitoring pain and knee flexion in youth athletes with growth-related lower-limb pathologies.